The decade of the electronic book - Živković, Daniela (Array, 2007)
The aim of the paper is to show the most important developments of the e-book in the last 10 years. Special emphasis is on the activities contributing to the creation of favorable condition for the production, distribution and reading electronic books. Successful information management with regard to e-books means defining the term e-book itself, developing identification systems, digital rights management and legal deposit as a part of digital libraries and cultural heritage.